Providing Education on Basic Life Support to Increase Student Knowledge - Billy, Billy Reihandi; Lintang Suryani, Roro; Murniati, Murniati (Global Indonesia Health Care (GOICARE), 2024)
Background: Basic Life Support (BLS) is an essential first aid action performed on individuals experiencing cardiac or respiratory arrest. The primary goal of BLS is to restore and maintain vital organ function through interventions like chest compressions and respiratory support. Knowledge, which arises from experience and observation, is enhanced through education. This process aims to improve understanding and, consequently, decision-making abilities. Purpose: The aim of this Community Service (PkM) project is to increase the knowledge of students at MAN 1 Banyumas regarding Basic Life Support. Method: The methods used in this PkM included lectures and discussions. The students' knowledge was assessed before and after the educational intervention using a structured knowledge questionnaire. Findings: The participants of this PkM were predominantly middle adolescents aged 15-17 years, with 29 participants (96.7%) falling within this age range. The majority were female, comprising 26 participants (86.7%). Most of the participants were in grade 11, accounting for 22 participants (73.3%). Before the educational intervention, the knowledge levels were as follows: Good: 2 participants (6.7%), Sufficient: 12 participants (40.0%), Poor: 16 participants (53.3%). After the BLS education, there was a marked improvement in knowledge, with all 30 participants (100%) achieving a